The Combination of Turmeric (Curcuma domestica) Rhizome Extract and Collagen in A Serum Formulation as an Antioxidant - Denia Pratiwi; Wahyu Margi Sidoretno; Nur Aisah (Borneo Journal of Pharmacy, 2021)
Turmeric (Curcuma domestica) has nutritious compounds called curcuminoids, which can be used as antioxidants. As an antioxidant, C. domestica extract can be used to ward off free radicals that damage collagen and elastin, a protein that keeps skin moist. This study aimed to determine the antioxidant activity of serum combined with collagen's addition using the DPPH method. The DPPH was made at a concentration of 80 μg/mL, and the absorption was read at a wavelength of 520 nm using a microplate rider. The study was conducted by making six formulations: F0, F1, F2, F3, F4, and F5 obtained the results of serum made from C. domestica extract that could inhibit free radicals and meet the physical evaluation test requirements of serum. Furthermore, the formula was made using only one active ingredient and only collagen to determine the extract or collagen's antioxidant activity. The results obtained indicate that collagen had a supporting role in adding antioxidant activity apart from its extract. The highest % inhibition value at F5 with 90.526% could ward off free radicals.